Wady sieci międzyorganizacyjnych - Niemczyk, Jerzy (Disadvantages of Inter-Organizational Networks, 2008)
Inter-organizational networks can take form of: franchising networks, outsourcing networks networks of independent agents, or co-operation networks. They dominated many sectors of modern economy. Many authors writing about inter-organizational networks emphasize their advantages. Rarely can be found scientific work concerning their weaknesses. Identification of potential shortcomings of networks reąuires reference point. Disadvantages can concern networks as a whole, concern their parts or they can be evalueted by the environment of networks (suppliers, customers, other networks or new companies). The purpose of this article is to present disadvantages of networks from those points of view. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 24, s. 176-182